2015
DOI: 10.1186/s13063-015-0930-8
|View full text |Cite
|
Sign up to set email alerts
|

Ghana randomized air pollution and health study (GRAPHS): study protocol for a randomized controlled trial

Abstract: BackgroundHousehold air pollution exposure is a major health risk, but validated interventions remain elusive.Methods/DesignThe Ghana Randomized Air Pollution and Health Study (GRAPHS) is a cluster-randomized trial that evaluates the efficacy of clean fuels (liquefied petroleum gas, or LPG) and efficient biomass cookstoves in the Brong-Ahafo region of central Ghana. We recruit pregnant women into LPG, efficient cookstove, and control arms and track birth weight and physician-assessed severe pneumonia incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 35 publications
0
69
0
Order By: Relevance
“…34,35 A pair of randomised controlled trials found little statistical evidence of a reduction in pneumonia incidence with provision of chimneys 36 or cleaner burning cookstoves, 37 and several more studies investigating household air pollution and childhood pneumonia are in progress. 38,39 This suggests that the provision of chimneys or cleaner burning practices does not result in a sufficient reduction of air pollution to translate into a reduction in health effects. This finding is consistent with the analysis and recommendations by the WHO guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 A pair of randomised controlled trials found little statistical evidence of a reduction in pneumonia incidence with provision of chimneys 36 or cleaner burning cookstoves, 37 and several more studies investigating household air pollution and childhood pneumonia are in progress. 38,39 This suggests that the provision of chimneys or cleaner burning practices does not result in a sufficient reduction of air pollution to translate into a reduction in health effects. This finding is consistent with the analysis and recommendations by the WHO guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, GRAPHS is a community-level clustered randomized controlled trial of a cookstove intervention in a predominantly rural area of Ghana (Jack et al 2015) (NCT01335490). Inclusion criteria for enrollment include being in the first or second trimester of pregnancy, living in one of 35 communities in the Kintampo Health Research Center (KHRC) catchment area, being the primary cook of the household, and being a non-smoker.…”
Section: Methodsmentioning
confidence: 99%
“…We will also seek to define local thresholds for oxyhaemoglobin saturation and respiratory rate at altitudes 2500 m above sea level. The HAPIN trial, the Ghana randomised air pollution and health study (GRAPHS), 117 and the Nepal trials 118 will inform the literature on the nature of the relationship between various definitions of pneumonia and household air pollution exposure in young children. The HAPIN definition focuses on severe pneumonia diagnosed by field workers using objective criteria (figure 1).…”
Section: Figure 2: Example Of a Framework Of Health-seeking Behaviourmentioning
confidence: 99%
“…The HAPIN definition focuses on severe pneumonia diagnosed by field workers using objective criteria (figure 1). The GRAPHS trial uses a physician assessed definition of severe pneumonia in the first year of life, 117 whereas the Nepal trials use the incidence of acute lower respiratory infection during the first 36 months of age, determined by maternal report and field worker assessment for more severe cases. 118 As study objectives differ based on the type of intervention and study setting, the pneumonia case definition and surveillance strategy should be carefully considered before implementing pneumonia outcome studies.…”
Section: Figure 2: Example Of a Framework Of Health-seeking Behaviourmentioning
confidence: 99%